2013
DOI: 10.1002/jat.2870
|View full text |Cite
|
Sign up to set email alerts
|

Uranium dynamics and developmental sensitivity in rat kidney

Abstract: Renal toxicity is the principal health concern after uranium exposure. Children are particularly vulnerable to uranium exposure; with contact with depleted uranium in war zones or groundwater contamination the most likely exposure scenarios. To investigate renal sensitivity to uranium exposure during development, we examined uranium distribution and uranium-induced apoptosis in the kidneys of neonate (7-day-old), prepubertal (25-day-old) and adult (70-day-old) male Wistar rats. Mean renal uranium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Other publications have noted histological lesions of rat kidneys, but at higher uranium exposure levels (200 mg/L, [43]; 30 mg/L, [55]). Recently, Homma-Takeda et al published deleterious effects of uranium in different rat models (neonate, prepubertal, and adult) after subcutaneous administration of uranium acetate [56]. The discrepancy is very likely due to the difference of the administration mode.…”
Section: Discussionmentioning
confidence: 99%
“…Other publications have noted histological lesions of rat kidneys, but at higher uranium exposure levels (200 mg/L, [43]; 30 mg/L, [55]). Recently, Homma-Takeda et al published deleterious effects of uranium in different rat models (neonate, prepubertal, and adult) after subcutaneous administration of uranium acetate [56]. The discrepancy is very likely due to the difference of the administration mode.…”
Section: Discussionmentioning
confidence: 99%
“…9 It was demonstrated that uranium specially accumulates in the S3 segment of the proximal tubule, mild renal tubular lesions was observed at a dose 0.5 mg/kg by subcutaneous injection exposure of rat to uranium acetate. 10 It was reported that maximal effect on kidney is seen after 5 d of uranyl acetate oral administration with dietary consumption ad libitum oral administration in Swiss albino mice. 11 A single dose of 5 mg/kg of uranyl nitrate induced renal damage after 2 d in C57 BI/6J mice has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…DU is a heavy metal and can emit α and ÎČ particles; thus, it exhibits both heavy metal toxicity and radiotoxicity. The kidney is the major target organ of acute DU exposure, and DU can cause severe necrosis of renal proximal tubule endothelial cells, ultimately leading to acute renal failure or even death345. The following mechanisms of action underlie the nephrotoxicity of DU6: (1) altering ion transport in cells to inhibit the oxidative phosphorylation of mitochondria and utilization of adenosine triphosphate (ATP); (2) altering the expression of certain genes (associated with inflammation, oxidative stress, and homeostasis); and (3) increasing oxidative stress levels and decreasing anti-oxidation in cells, thus increasing DNA damage and promoting apoptosis.…”
mentioning
confidence: 99%